1979 Híjole Mano - Circo Maroma Teatro (2017)
Elenco: Bertha Iriart, Alejandra Dorantes, Jaime Ruiz, Norma del Rivero, María Sague, Otto Minera | Vestuario: Arnoldo Federico | Escenografía: Gabriel Ruiz | Dirección: Paco Giménez